Sistema de gestión de calidad para profesionales independientes y mipymes de construcción (2021)
Construction is one of the main regions of the economy, for the good performance of construction companies it is necessary to comply with the regulations that govern the construction of buildings and have a system that guarantees the quality of the execution of civil works, the safety at work, and protection of the environment. Starting with the ISO 9000 version of 1994, the Organization for Standardization-ISO-International Organization for Standardization based in Geneva, dependent on the United Nations United Nations, contributes to the greater growth of the ISO 9001, ISO 14001 and OHSAS, which are a tool that allows order and traceability in the different processes of each project.